Impact of Duty Briefing on Aviation Safety Services at AirNav Indonesia Palembang Branch - Pitria Herni Juita; Martha Saulina; Susi Suhardianti (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Safety is a fundamental principle that cannot be compromised in air navigation services, as it represents the highest priority in every operational aspect. Air Traffic Controllers (ATC) play a crucial role in preventing aircraft collisions, avoiding obstacles, and ensuring overall operational safety. Therefore, the proper execution of ATC duties in accordance with standard procedures is essential. This study aims to analyze the effect of duty briefing on aviation safety services at Perum LPPNPI Palembang Branch. A quantitative research method was employed, with data collected through structured questionnaires distributed to ATC personnel. The research sample consisted of 50 respondents, and the data were analyzed using Statistical Package for Social Science (SPSS) version 26. Instrument testing showed that all questionnaire items were valid and reliable. The analysis results indicate a positive and significant relationship between duty briefing and aviation safety services, with duty briefing contributing substantially to the improvement of safety performance.